FRB121102: First detection across 5 - 8 GHz and spectral properties from the Breakthrough Listen instrument - Gajjar, V.; Siemion, A.; MacMohan, D.; Croft, S.; Hellbourg, Gregory; Isaacson, H.; Enriquez, J.; Price, D.; Lebofsky, M.; De Boer, D.; Werthimer, D.; Hickish, J.; et al. (2018)
No Abstract Available